2016
DOI: 10.1074/jbc.m115.699546
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol-mediated Degradation of 7-Dehydrocholesterol Reductase Switches the Balance from Cholesterol to Vitamin D Synthesis

Abstract: Cholesterol is detrimental to human health in excess but is also essential for normal embryogenesis. Hence, enzymes involved in its synthesis possess many layers of regulation to achieve balanced cholesterol levels. 7-Dehydrocholesterol reductase (DHCR7) is the terminal enzyme of cholesterol synthesis in the Kandutsch-Russell pathway, converting 7-dehydrocholesterol (7DHC) to cholesterol. In the absence of functional DHCR7, accumulation of 7DHC and a lack of cholesterol production leads to the devastating deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
79
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(89 citation statements)
references
References 58 publications
1
79
0
2
Order By: Relevance
“…The regulation of DHCR7 is incompletely understood. Cholesterol and vitamin D (but not 1,25(OH) 2 D) increase proteasomal degradation of DHCR7, as does UVB, leading to increased vitamin D production . AMPK, a key sensor and regulator of cellular energy homeostasis, and protein kinase A are potent inhibitors of DHCR7, whereas CaMKII has a lower inhibitory effect .…”
Section: ‐Dehydrocholesterol Reductase (Dhcr7)mentioning
confidence: 99%
See 1 more Smart Citation
“…The regulation of DHCR7 is incompletely understood. Cholesterol and vitamin D (but not 1,25(OH) 2 D) increase proteasomal degradation of DHCR7, as does UVB, leading to increased vitamin D production . AMPK, a key sensor and regulator of cellular energy homeostasis, and protein kinase A are potent inhibitors of DHCR7, whereas CaMKII has a lower inhibitory effect .…”
Section: ‐Dehydrocholesterol Reductase (Dhcr7)mentioning
confidence: 99%
“…Cholesterol and vitamin D (but not 1,25(OH) 2 D) increase proteasomal degradation of DHCR7, as does UVB, leading to increased vitamin D production. (30) AMPK, a key sensor and regulator of cellular energy homeostasis, and protein kinase A are potent inhibitors of DHCR7, whereas CaMKII has a lower inhibitory effect. (31,32) Most textbooks and reviews clearly state that the photochemical production of vitamin D in the skin is a nonenzymatic reaction.…”
Section: -Dehydrocholesterol Reductase (Dhcr7)mentioning
confidence: 99%
“…Thus, clinical approaches for this currently incurable disease include ways to elevate DHCR7 levels in patients. Recent work (e.g., by Prabhu et al 2016) indicated that DHCR7 is subject to cholesterol-regulated degradation. Elevating the level of cholesterol in cultured mammalian cells causes selective degradation by the proteasome.…”
Section: Smith-lemli-opitz Syndromementioning
confidence: 99%
“…When cholesterol in the ER exceeds 5 mole% of total ER lipids, the ER‐to‐Golgi transport of the SREBP/SCAP complex is rapidly blocked, preventing the transcription of genes involved in cholesterol biosynthesis and uptake . High level of cholesterol in ER membranes also accelerates the proteasomal degradation of key enzymes of cholesterol biosynthetic pathway, such as 3‐hydroxy‐3‐methylglutaryl‐CoA reductase (HMGCR), squalene monooxygenase and 7‐dehydrocholesterol reductase . In addition, excess free cholesterol activates ACAT allosterically, resulting in the production of cholesteryl esters that are stored together with triacylglycerols in the lipid droplets …”
Section: Cholesterol Transport From Les/lys To the Ermentioning
confidence: 99%
“…57,58 High level of cholesterol in ER membranes also accelerates the proteasomal degradation of key enzymes of cholesterol biosynthetic pathway, such as 3hydroxy-3-methylglutaryl-CoA reductase (HMGCR), 59,60 squalene monooxygenase 61 and 7-dehydrocholesterol reductase. 62 In addition, excess free cholesterol activates ACAT allosterically, resulting in the production of cholesteryl esters that are stored together with triacylglycerols in the lipid droplets. 63,64 While LDL-cholesterol can reach the ER by vesicular trafficking, most likely through the trans-Golgi network (TGN) (as discussed later), there has been increasing appreciation that the tubular ER network is closely apposed to almost all LEs in the cell.…”
Section: Cholesterol Transport From Les/lys To the Ermentioning
confidence: 99%